1993
DOI: 10.1002/jbm.820270712
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene chemistry affects vitronectin activity: An explanation for cell attachment to tissue culture polystyrene but not to unmodified polystyrene

Abstract: Tissue culture polystyrene (TCPS) supports good attachment of adherent cells whereas unmodified polystyrene (PS) does not, but the mechanism of this difference is not well characterized. We have compared TCPS and PS for the amounts of vitronectin (Vn) and fibronectin (Fn) which adsorb from the fetal bovine serum (FBS) component of the culture medium. The significance of the amounts of Vn and Fn which adsorbed onto TCPS and PS was determined by reference to the concentration dependence of the cell attachment ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 46 publications
6
103
3
Order By: Relevance
“…Cell adhesion to several material surfaces is dependent on the prior adsorption of specific serum proteins, including fibronectin and vitronectin, 53 which support cell attachment to the surface and influence cell morphology. [54][55][56] In this study, we demonstrated that hMSC morphology was affected by the underlying surface topography, specifically in terms of cell spread and the number of filopodia. Differences in the amount of serum proteins deposited on the investigated surfaces may account for the observed variation in cell morphology.…”
Section: Discussionmentioning
confidence: 71%
“…Cell adhesion to several material surfaces is dependent on the prior adsorption of specific serum proteins, including fibronectin and vitronectin, 53 which support cell attachment to the surface and influence cell morphology. [54][55][56] In this study, we demonstrated that hMSC morphology was affected by the underlying surface topography, specifically in terms of cell spread and the number of filopodia. Differences in the amount of serum proteins deposited on the investigated surfaces may account for the observed variation in cell morphology.…”
Section: Discussionmentioning
confidence: 71%
“…However, ␣ v ␤ 3 integrin is a major contributor in adhesion of HSCs to tissue culture plastic as our previous studies showed that echistatin effectively blocks adhesion of HSCs to this substrate (31). The HSCs in our studies were routinely plated in media containing relatively high concentrations of FCS, a rich source of soluble fibronectin and vitronectin, which bind to tissue culture plastic and might act as an ␣ v ␤ 3 -dependent adhesive layer for the cells (60).…”
Section: Discussionmentioning
confidence: 92%
“…Subsequently, vitronectin was specifically bound via the corresponding epitope recognized by the solidphase antibody. Immobilizing vitronectin in an immunospecific fashion such as this avoids conformational perturbations that are known to occur when vitronectin is adsorbed to plastic surfaces (37)(38)(39). This was reasoned to be a better approach for testing effects of blocking both epitopes on vitronectin because all vitronectin bound to the solid-phase is, by design, blocked at one epitope.…”
Section: Monoclonal Antibodies Specific For Different Epitopes On Vitmentioning
confidence: 99%